Functional Magnetic Resonance Imaging - Huettel, Scott A.; Song, Allen W.; McCarthy, Gregory (New York: Sinauer, 2014)
Functional Magnetic Resonance Imaging was the first textbook to provide a true introduction to fMRI--one that presented material authoritatively and comprehensively, yet was accessible to undergraduate students, graduate students, and beginning researchers. This third edition features an updated discussion of the physiological basis of fMRI that includes recent discoveries about the origins of the BOLD response, new data-driven and computational approaches to fMRI data analysis, explanations of creative approaches to experimental design, and discussions of ethical and methodological controversies, among many other revisions. Examples are drawn both from seminal historical work and cutting-edge current research. Concepts are reinforced by numerous thought problems and illustrated with full-color figures, all revised for this edition to achieve a contemporary graphic look. Each chapter is accompanied by updated references and suggested readings.
Glossary G-1-G-16p.; Index I-1-I-16p.
Keywords: Advanced MRI methods; Experimental design; MRI Scanners; Cognitive neuroscience